One-step synthesis of single-site vanadium substitution in 1T-WS2 monolayers for enhanced hydrogen evolution catalysis - Ali Han (Nature Portfolio, 2021)
Ru is one of the most active metals for oxygen evolution reaction, but it quickly dissolves in acidic electrolyte particularly in nanosized form. Here the authors show that coral-like solid-solution Ru‒Ir consisting of 3 nm-thick sheets with only 6 at% Ir is a long-lived catalyst with high activity